2021
DOI: 10.6007/ijarbss/v11-i13/8522
|View full text |Cite
|
Sign up to set email alerts
|

TVET Graduate Employability: Mismatching Traits Between Supply and Demand

Abstract: Polytechnic programmes in Malaysia were established to produce quality graduates at the semi-professional level in engineering, trade, hospitality, ICT and services, as well as, to provide alternative pathways for TVET students in the higher education. According to the Ministry of Education, even though Polytechnic graduate employability is at 96.7%, the tourism management programmes in Polytechnics have an average of 51% employability upon graduation, and these deficiencies need to be identified and studied s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 44 publications
(45 reference statements)
0
5
0
Order By: Relevance
“…The above issue is also driven by the employers' perception that HEI does not bestow TVET graduates' job-ready skills. Although TVET graduates possessed specialised knowledge and hard skills, they did not have the soft skills needed to create jobs (Ismail, Chik, & Hemdi, 2021). Recent research identified several soft skills elements such as entrepreneurial, teamwork, communication, career adaptability, and problem-solving skills that are important in preparing and prompting graduates to use their existing talents to become entrepreneurs (Dwi Riyanti, Sandroto, & Warmiyati, 2016).…”
Section: Research Backgroundmentioning
confidence: 99%
“…The above issue is also driven by the employers' perception that HEI does not bestow TVET graduates' job-ready skills. Although TVET graduates possessed specialised knowledge and hard skills, they did not have the soft skills needed to create jobs (Ismail, Chik, & Hemdi, 2021). Recent research identified several soft skills elements such as entrepreneurial, teamwork, communication, career adaptability, and problem-solving skills that are important in preparing and prompting graduates to use their existing talents to become entrepreneurs (Dwi Riyanti, Sandroto, & Warmiyati, 2016).…”
Section: Research Backgroundmentioning
confidence: 99%
“…This shows the imbalance between supply and demand in Malaysia, resulting in not enough TVET graduates in Malaysia (Dzeto, 2014;Abdullah, Salleh, Sulaiman & Kamarrudin, 2022). Nonetheless, Ismail, Chik, and Hemdi (2021) suggested that strengthening the TVET curriculum in Malaysia is one of the solutions to address the TVET labour supply-demand imbalance, and the researchers also suggested that TVET courses could focus on 70% of practice training and 30% to ensure that the TVET program produces a skilled, capable and competitive workforce in the labour market whose employable skills play a relevant role in job readiness and career development.…”
Section: Vocational College Curriculummentioning
confidence: 99%
“…Furthermore, Ismail et al. (2021) posit that the aforementioned issue has become a concern because due to skill mismatches, many graduates are not skilfully aligned with most of the jobs available and thus could contribute to a serious unemployment problem in the country (Azmi et al., 2018), subsequently creating an imbalance between workforce supply and demand [Institute of Labour Market Information and Analysis (ILMIA), 2018; Ministry of Finance (MoF), 2020, cited in Ismail et al., 2021].…”
Section: Literature Reviewmentioning
confidence: 99%